Analisis Permainan Lompat Tali untuk Meningkatkan Kemampuan Motorik Anak di Sekolah Dasar - Khairu Ulfa Barus; Mawar Sari; Nurul Aulia; Bunga Salsabila; Anggi Pratiwi; Adinda Najwa; Dina Thahura Azzahra; Nabila Pratama Putri; Sri Lestari; Desi Nurhalimah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study uses a literature review method to examine the role of jump rope activities in improving coordination, balance, agility, and strength among elementary school children. It provides an in-depth analysis of jump rope games in the context of enhancing motor skills in elementary education. The study explores how this traditional game can serve as an effective tool for developing various motor skills in children. It covers the types of motor skills involved in jump rope activities, variations of the game, as well as the physical and non-physical benefits gained. The study also highlights the important role of physical education teachers in optimizing students’ motor development through traditional games. The results indicate that jump rope activities are not only beneficial for the development of gross and fine motor skills but also possess significant social and cultural value. These games can instill values such as discipline, perseverance, hard work, and cooperation in children. It is expected that this study will contribute to the development of more effective and innovative physical education learning.